EFFECT OF ENZYME TREATMENT ON GUAVA JUICE PRODUCTION USING RESPONSE SURFACE METHODOLOGY - A. Akesowan; A. Choonhahirun (Journal of Animal and Plant Sciences, 2013)
Response surface methodology (RSM) was used to investigate the effects of enzyme concentration (500-900 ppm) and incubation time (30-90 min) on viscosity of guava puree and pH, titratable acidity, clarity, yield, total soluble solid (TSS) and ascorbic acid of guava juice. In addition, the numerical optimization was conducted to find the best enzyme condition. The result indicated that the enzyme treatment reduced guava puree viscosity, promoted juice clarification and increased values for titratable acidity, yield, TSS and ascorbic acid of guava juice than that without enzyme. Only regression models of guava puree viscosity, yield, TSS and ascorbic acid with coefficient of determination (R 2) of 0.9706, 0.9785, 0.9678 and 0.9687, respectively were significant, reliable and suitable to describe the experimental data. Increasing of enzyme concentration and incubation time decreased puree viscosity and increased yield, TSS and ascorbic acid. Enzyme concentration was the most significant variable affecting these properties. The optimal enzyme treatment recommended to add 869.36 ppm pectinase in guava mash and incubated for 71.27 min before filtration process. Under this condition, predicted puree viscosity, yield, TSS and ascorbic acid were 160.07 cps, 85.10%, 5.60 Brix and 54.27 mg/100 ml, respectively. In conclusion, the development of guava juice quality can be achieved by pectinase application. The RSM successfully revealed that increasing of enzyme concentration and incubation time related to decreased guava puree viscosity and increased yield, TSS and ascorbic acid of guava juice. The usage of proper pectinase concentration and incubation time would be an approach to enhance guava juice characteristics.
Keywords: Guava juice processing; enzyme treatment; pectinase; response surface methodology